Research advancements in pharmaceutical, nutritional, and industrial enzymology - Bharati, Shashi Lata, 1983-; Chaurasia, Pankaj Kumar, 1987- (Medical Information Science Reference (an imprint of IGI Global), 2018)
"This book provides the significant applications of enzymes in the field of pharmaceutical chemistry. It explores the pharmaceutical knowledge and research on enzymes. It provides information regarding pharmaceutical enzymology that will be very useful for the researchers working on such topics of biological importance"--Provided by publisher.